The Role Of Volatility In Mediating The Impact Of Analyst’ Recommendations On Herding In The Malaysian Stock Market - Ooi, Kok Loang (2023)
This thesis examines the role of volatility in mediating the relationship between analyst recommendations and herding in the Malaysian stock market from 2015 to 2021. Herding has been found as one of the causes of securities mispricing due to the collective behaviour of pushing prices away from fundamentals. Herding is often associated with financial crises due to information cascades or abandoning private information to follow the crowd. Nonetheless, the role of analyst recommendations in affecting herding can be too good to be true without considering the mediating role of volatility that triggers the investors’ emotions to make investment decisions. Hence, this study explores the existence of herding in the market and examines the impact of analyst recommendations on herding. For methodology, this study adopts the Cross-Sectional Standard Deviation (CSSD) by Chang, Cheng and Khorana (2000) and Cross-Sectional Absolute Deviation (CSAD) by Chiang and Zheng (2010) in the panel data and quantile regressions to detect herding. Based on the Baron and Kenny (1986) mediation model, the results show that herding exists in the Malaysian stock market, and volatility mediates the relationship between analyst recommendations and herding. Realized volatility is the only volatility measurement significant to analyst recommendations and herding because investors rely on the previous day’s stock price as the benchmark to trade. Besides, the dispersion of target price is the only variable of analyst recommendations shown to be significant to stock price volatility and herding. The result of the quantile regression indicates that herding is more pronounced in the upper quantile of CSAD.